Bottom and Intermediate Nepheloid Layer Induced by Shoaling Internal Solitary Waves: Impacts of the Angle of the Wave Group Velocity Vector and Slope Gradients. Issue 8 (14th August 2019) - Tian, Zhuangcai; Jia, Yonggang; Zhang, Shaotong; Zhang, Xiaojiang; Li, Yang; Guo, Xiujun
Abstract: The widely recognized global phenomena of bottom nepheloid layer (BNL) and intermediate nepheloid layer (INL) are ubiquitous in the ocean. These phenomena are induced by shoaling internal solitary waves (ISWs), as observed in many studies. In this study, we analyzed the BNLs and INLs induced by shoaling ISWs and their detailed processes using flume experiments and field observations. ISWs suspended seabed sediment by the horizontal velocity in the vortex, and the near‐bottom vertical velocity lifted sediment into the water column to create a BNL, which detached from the slope and diffused along the isopycnals, forming more than one INL. Considering the results of previous researchers, we found that the numbers of BNLs and INLs were principally determined by the relationship between the angle of the ISW group velocity vector (α) relative to horizontal and the slope gradients (γ). In transmissive regions (γ/α < 1), one BNL and more than one INL were formed. In critical regions (γ/α 1), only one BNL and less than one INL were observed. In reflective regions (γ/α > 1), less than one BNL was formed and no INL. The BNL in the critical regions should be the thickest where the sediment resuspension was the greatest. The concentrations and thicknesses of BNLs and INLs were related to the energy and amplitude of ISW and the sediment condition. The results in the transmissive regions were proved by field observation. Our research will help to predict the number and magnitude of transport channels formed by shoaling ISWs from the ocean margin to the ocean interior. Key Points: Bottom and intermediate nepheloid layer induced by shoaling internal solitary waves were predicted with the theory of linear wave refraction The number of bottom and intermediate nepheloid layers was principally determined by the relationship between the angle of the ISW group velocity vector and slope gradients Horizontal velocity resuspended sediment, and vertical velocity lifted sediment into water column, creating a bottom nepheloid layer, which detached from the slope and diffused along isopycnals, forming intermediate nepheloid layers